2017
DOI: 10.1016/j.ajoc.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor-positive ductal adenocarcinoma of the nasolacrimal duct: A case report

Abstract: PurposePrimary ductal adenocarcinoma arising in the structures of the lacrimal apparatus is extremely rare, and the entity is considered a lacrimal counterpart of salivary duct carcinoma, of which the majority are known to express androgen receptor (AR). Less than 10 cases of AR-positive carcinomas of lacrimal gland or lacrimal sac have been described.ObservationsWe present a primary ductal adenocarcinoma with AR expression involving the nasolacrimal duct of a middle-aged patient who had suffered from right ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Androgens regulate the proliferation rates of epithelial cells, so increased androgen levels or AR activity could result in unlimited proliferation and cancer development. AR is required for normal prostate function and is expressed in prostatic intra-epithelial neoplasias (PIN) and early carcinoma; however, it is also expressed in advanced and metastatic carcinoma (18) . We performed a cross-section analytical study at the pathology department of the Faculty of Medicine at Suez Canal University.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens regulate the proliferation rates of epithelial cells, so increased androgen levels or AR activity could result in unlimited proliferation and cancer development. AR is required for normal prostate function and is expressed in prostatic intra-epithelial neoplasias (PIN) and early carcinoma; however, it is also expressed in advanced and metastatic carcinoma (18) . We performed a cross-section analytical study at the pathology department of the Faculty of Medicine at Suez Canal University.…”
Section: Discussionmentioning
confidence: 99%
“…Two corneal lesions were reported as ocular adverse effects of T-DM1 administration [5, 6] based on the expression of HER2 in corneal epithelial cells and its susceptibility to trastuzumab harboring agents. In literature, two studies have reported HER2 overexpression in adenocarcinoma of lacrimal sac and nasolacrimal duct [11, 12], but not in normal nasolacrimal epithelium. If HER2 is also expressed in the normal nasolacrimal epithelium, nasolacrimal stenosis in our case can be explained in part as an effect of trastuzumab.…”
Section: Discussionmentioning
confidence: 99%